PERLINDUNGAN HUKUM BAGI PENGGUNA JASA DRY CLEAN & LAUNDRY SERVICE TERHADAP HAK KONSUMEN (STUDI PUTUSAN NOMOR 85/PDT.G/2019/PN.JKT.PST) - Maya Adilla Humaira; Ariawan Gunandi (Fakultas Hukum Universitas Tarumanagara, 2021)
Legal protection for consumers is very important because basically consumers have the same rights as business actors, both universal and specific rights. In Article 1 number 1 of Law Number 8 of 1999 concerning Consumer Protection, namely all efforts to ensure legal certainty to provide protection to consumers. Consumer protection is a legal instrument created to protect and fulfill consumer rights or efforts to ensure legal certainty to provide protection to consumers.